2021
DOI: 10.3748/wjg.v27.i46.7866
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the chemotherapy-induced hepatic damage: Yellow liver, blue liver, and pseudocirrhosis

Abstract: The liver is the major drug-metabolizing and drug-detoxifying organ. Many drugs can cause liver damage through various mechanisms; however, the liver response to injury includes a relatively narrow spectrum of alterations that, regardless of the cause, are represented by phlogosis, oxidative stress and necrosis. The combination of these alterations mainly results in three radiological findings: vascular alterations, structural changes and metabolic function reduction. Chemotherapy has changed in recent decades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 156 publications
(263 reference statements)
1
9
0
Order By: Relevance
“…Our analysis might confirm this association in patients with PH on chemotherapy and sinusoidal obstruction syndrome 40 . Both the two conditions would fall within the sinusoidal forms of hepatic outflow obstruction, as a consequence of endothelial damage to the sinusoids, and the pattern of enhancement of the peliotic lacunae could depend on the site and extension of the sinusoidal wall rupture 59,60 . Thus, we hypothesize that if the damage is essentially located around an arterial vessel, the lesion might show a homogeneously high persisting enhancement or a progressive centrifugal enhancement with an arterial target sign.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our analysis might confirm this association in patients with PH on chemotherapy and sinusoidal obstruction syndrome 40 . Both the two conditions would fall within the sinusoidal forms of hepatic outflow obstruction, as a consequence of endothelial damage to the sinusoids, and the pattern of enhancement of the peliotic lacunae could depend on the site and extension of the sinusoidal wall rupture 59,60 . Thus, we hypothesize that if the damage is essentially located around an arterial vessel, the lesion might show a homogeneously high persisting enhancement or a progressive centrifugal enhancement with an arterial target sign.…”
Section: Discussionsupporting
confidence: 60%
“…59,60 Thus, we hypothesize that if the damage is essentially located around an arterial vessel, the lesion might show a homogeneously high persisting enhancement or a progressive centrifugal enhancement with an arterial target sign. Conversely, if the damage is predominantly located around a dilated central vein, the PH nodule might show an arterial peripheral rim enhancement with progressive centripetal or heterogeneous nonspecific patterns.…”
mentioning
confidence: 99%
“…Other studies have suggested that a direct hepatotoxic effect of chemotherapy treatment may play a role, and some have implicated specific agents such as paclitaxel, trastuzumab, tamoxifen, regorafenib, and palbociclib [ 2 , 37 , 45 , 62 ]. Interruption or pause of chemotherapy may result in resolution of imaging features of pseudocirrhosis [ 63 ]. Kang et al describe a case of pseudocirrhosis in which cessation of chemotherapy resulted in improvement of portal hypertensive complications, lab abnormalities, and near resolution of cirrhotic liver appearance on imaging [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported by Calistri et al, BL referred to parenchymal venous congestion resulting from blockage of blood outflow, macroscopically characterized by an intraoperative subcapsular livid appearance and a similar “marble” bluish‐red discoloration on the cut surface. 9 Therefore, three or more surgeons determined the presence or absence of oxaliplatin‐associated BL by confirming the color of the liver during the operation. 10 , 11 The findings of BL in this study are shown in Figure S1 .…”
Section: Methodsmentioning
confidence: 99%